2014
DOI: 10.3892/ijo.2014.2705
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of CRMP4, a new prostate cancer metastasis suppressor gene, inhibits tumor growth in a nude mouse intratibial injection model

Abstract: Prostate cancer, the most commonly diagnosed male cancer in North America, has a high incidence of bone metastasis. Our previous study showed collapsin response mediator protein 4 (CRMP4) gene inhibited prostate cancer migration and invasion. In this study, we investigated whether overexpression of CRMP4 gene in prostate cancer cells inhibit tumor bone metastasis. The stable prostate cancer cells overexpressing the CRMP4 gene were constructed using lentivirus infection. Prostate cancer bone metastasis nude mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
(42 reference statements)
1
9
1
Order By: Relevance
“…We found that CRMP4a overexpression and CRMP4b silencing suppressed gastric carcinoma cell proliferation, migration, cell cycle progression, invasion, and adhesion, but did not affect apoptosis. These results differ from those of prior studies on prostate and pancreatic cancer: CRMP4 had no effect on cell proliferation in either of these cancers [ 20 , 22 ]. Consistent with the results of previous studies on prostate and pancreatic cancer, we found that CRMP4a and CRMP4b play an important role in regulating cell migration and invasion.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found that CRMP4a overexpression and CRMP4b silencing suppressed gastric carcinoma cell proliferation, migration, cell cycle progression, invasion, and adhesion, but did not affect apoptosis. These results differ from those of prior studies on prostate and pancreatic cancer: CRMP4 had no effect on cell proliferation in either of these cancers [ 20 , 22 ]. Consistent with the results of previous studies on prostate and pancreatic cancer, we found that CRMP4a and CRMP4b play an important role in regulating cell migration and invasion.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, CRMP4a (TUC-4a) and CRMP4b (TUC-4b) exhibit opposing functions in neurite outgrowth [ 6 , 19 ]. In addition, altered CRMP4 expression has been observed in several malignant tumors, including prostate cancer, pancreatic cancer, and neuroblastoma [ 14 , 20 22 ]. In prostate cancer, CRMP4 expression was inversely associated with lymph node metastasis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our studies demonstrated that expression of CRMP4a, the shorter splicing variant, is significantly lower in metastatic prostate cancers than that in primary cancers at the mRNA and protein levels and that CRMP4a overexpression drastically suppressed cell migration and tumor metastasis in prostate cancer models 8 . Additionally, using the small activating RNA (saRNA) technique, we demonstrated that enhancement of CRMP4a expression completely blocked distant metastases in mouse xenograft models of prostate cancer 9 , which has been supported by others utilizing different approaches 10,11 .…”
Section: Introductionsupporting
confidence: 60%
“…As a member of the CRMP family of cytosolic phosphoproteins, CRMP-4 serves a crucial function in the mediation of semaphorin/collapsin-induced growth cone collapse and regulating the neuronal development and myelin-dependent axon outgrowth ( 20 ). Differential expression of CRMP-4 has been observed in numerous types of malignancy ( 21 , 22 ). For example, CRMP-4 was differentially expressed in pancreatic cancer tissues and CRMP-4 silencing reduced cellular invasion, which indicates that CRMP-4 is significantly associated with poor prognosis by promoting liver metastasis and may serve as a novel therapeutic target for pancreatic cancer ( 15 ).…”
Section: Discussionmentioning
confidence: 99%